Comparative analysis of sustainable desiccant – Evaporative based ventilation systems for a typical Qatari poultry house. (1st October 2021) - Harrouz, Jean Paul; Katramiz, Elvire; Ghali, Kamel; Ouahrani, Djamel; Ghaddar, Nesreen
Graphical abstract: Highlights: Two sustainable cooling systems are proposed for poultry houses in hot/humid climates. System I: solid desiccant bed integrated with Direct Evaporative Cooler. System II: solid desiccant bed integrated with Dew-Point Indirect Evaporative Cooler. The performance of each system was optimized to reduce the operation cost. System II resulted in 35 % reduction in the operating cost as compared to system I. Abstract: Direct evaporative cooling is the typically adopted ventilation system in poultry houses in hot climates. This type of cooling is inefficient during period of relatively high humidity resulting in degraded thermal comfort and air quality for the chicken. This work investigates two sustainable ventilation systems that are adequate to hot and humid climates to enhance the poultry indoor conditions. System I consists of the conventional direct evaporative cooler integrated with packed bed desiccant dehumidifier whilst system II integrates a dew-point indirect evaporative cooler with the packed desiccant bed. To determine the most cost-effective cooling system and ventilation strategy, both systems were sized and their operation optimized for a case study of a typical modular poultry house in Qatar hot humid climate. The selection of the better performing system was based on the consumption of water, electricity and thermal energy during the cooling season while ensuring that the same thermal and air quality conditions were attained within the poultry house by both systems. This was achieved by developing and validating mathematical models for the mass and energy balances of the poultry house as well as the systems' subcomponents. The models were integrated and a genetic algorithm optimizer was used to find the best performance of system I and system II to compare their performance. Accordingly, it was found that system II was able to meet the poultry house thermal and air quality requirements at 35 % lower operating cost as compared to system I over the entire Qatari cooling season.